A Critical Discourse Analysis of Isaac Herzog’s Speech on the U.S. Congress toward the War Against Palestine - Ong, Celine Sekar Nathania Purnama; Rahayu, Famala Eka Sanhadi; Prafitri, Wilma (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2025)
The emergence of conflicts in various countries has been arising in the past few years. A country’s leader is one of the important factors in determining the continuance of conflicts. Their language influences both their own people and the parties who are not directly involved in the conflict. Isaac Herzog’s ceremonial address at the U.S. Congress in 2023 can be used to analyse the rhetorical strategies in influencing the U.S. committee in the conflict with Palestine. Using Norman Fairclough’s three dimensions Critical Discourse Analysis model, the goal of this study is to reveal how the speaker exercises power in speech and influences their audience, by analysing the text from its textual, discursive, and social dimensions. The method used is a descriptive qualitative approach. The result of this study found the rhetorical strategy in shaping and influencing audiences, such as topic control through strategic lexical choices that frame actors ideologically, Intertextuality references that aligns with audience values to increase persuasion, and utilize sociocultural context to justify ideologies and actions. This analysis emphasized the importance of language in maintaining power, and rhetorical strategies in political discourse as tools for ideologies transfer and preservation.